Odpowiedzi

2009-11-06T17:02:17+01:00
3,5+1/27 *( 2/3 * 5 - 1) -2 * 5/3 =3,5+1/27*2i1/3-3i1/3=3,5+7/81-3i1/3=41/162
2009-11-06T17:02:48+01:00
3,5+1/27*(2/3*5-1)-2*5/3=3,5+1/27*(10/3-1)-10/3=3,5+1/27*2i1/3-10/3=
3,5+1/27*7/3-10/3=35/10+7/81-10/3=35/10+7/81-270/81=dokończ sobie
Najlepsza Odpowiedź!
2009-11-06T17:04:26+01:00
3,5+1/27 *( 2/3 * 5 - 1) -2 * 5/3 =35/10+1/27*(10/3-1/1)-2*5/3=35/10+1/27*7/3-10/3=3 i 5/10 +7/81=3 i 405/810 + 70/810-10/3=3 i 475/810-10/3=3 i 95/162-10/3=3i 95/162-540/162=581/162-540/162=41/162